2015
DOI: 10.1111/bjd.14281
|View full text |Cite
|
Sign up to set email alerts
|

Species identification of dermatophytes in paraffin-embedded biopsies with a new polymerase chain reaction assay targeting the internal transcribed spacer 2 region and comparison with histopathological features

Abstract: Molecular species identification of dermatophytes via ITS2 PCR can easily be implemented in a routine dermatopathology setting. It is fast and highly specific and improves the sensitivity of histopathological diagnosis of dermatophytosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
0
12
0
4
Order By: Relevance
“…However, it is impossible to determine the fungal genus or species based on the morphology of hyphae and spores in the tissue. Some studies have shown that fungal structures detected by histology may possibly also be identified and differentiated by NATs on formalin-fixed and paraffin-embedded nail and skin tissue (e. g., pathogenic dermatophyte species) [4].…”
Section: Confirmation and Pathogen Identification (Species) In Case Omentioning
confidence: 99%
“…However, it is impossible to determine the fungal genus or species based on the morphology of hyphae and spores in the tissue. Some studies have shown that fungal structures detected by histology may possibly also be identified and differentiated by NATs on formalin-fixed and paraffin-embedded nail and skin tissue (e. g., pathogenic dermatophyte species) [4].…”
Section: Confirmation and Pathogen Identification (Species) In Case Omentioning
confidence: 99%
“…Eckert et al used a new PCR assay targeting the ITS 2 region for identification of dermatophytes in paraffin‐embedded biopsies. They compared the results with histopathological investigation of the skin tissue.…”
Section: Discussionmentioning
confidence: 99%
“…However, we could not cultivate or isolate any species. We therefore attempted molecular identification of formalin‐fixed, paraffin‐embedded (FFPE) biopsy specimens . Fungal DNA was extracted from five thin‐sectioned FFPE tissue samples, each section approximately 10 μm, using a QIAamp DNA FFPE Tissue Kit (catalog no.…”
Section: Case Reportmentioning
confidence: 99%